Self-management of asthma in general practice, asthma control and quality of life: a randomised controlled trial. Issue 1 (1st January 2003) - Thoonen, B P A; Schermer, T R J; van den Boom, G; Molema, J; Folgering, H; Akkermans, R P; Grol, R; van Weel, C; van Schayck, C P
Abstract : Background: A study was undertaken to determine the effectiveness of asthma self-management in general practice. Methods: Nineteen general practices were randomly allocated to usual care (UC) or self-management (SM). Asthma patients were included after confirmation of the GP diagnosis. Follow up was 2 years. Patients kept diary cards and visited the lung function laboratory every 6 months. Outcomes were number of successfully treated weeks, limited activity days, asthma specific quality of life, forced expiratory volume in 1 second (FEV1 ), FEV1 reversibility, concentration of histamine provoking a fall in FEV1 of 20% or more (PC20 histamine), and amount of inhaled steroids. Results: A total of 214 patients were included in the study (104 UC/110 SM; one third of the total asthma population in general practice); 62% were female. The mean percentage of successfully treated weeks per patient in the UC group was 72% (74/103 weeks) compared with 78% (81/105 weeks) in the SM group (p=0.003). The mean number of limited activity days was 1.2 (95% CI 0.5 to 1.9) in the SM group and 3.9 (95% CI 2.5 to 5.4) in the UC group. The estimated increase in asthma quality of life score was 0.10 points per visit in the UC group and 0.21 points per visit in the SM group (p=0.055). FEV1, FEV1 reversibility, and PC20 histamine did not change. There was a saving of 217 puffs of inhaled steroid per patient in favour of the SM group (p<0.05). Conclusion: Self-management lowers the burden of illness as perceived by patients with asthma and is at least as effective as the treatment usually provided in Dutch primary care. Self-management is a safe basis for intermittent treatment with inhaled corticosteroids.